Utilising digital technology to personalise learning: how to influence non-urban East Malaysian undergraduates’ intention? / Noraisikin Sabani ... [et al.] - Sabani, Noraisikin; Salleh, Sallimah; Jimmi, Anita; Abdullah, Shamsul Kamariah (UiTM Press, 2024)
The focus of this study is to investigate East Malaysian undergraduates’ behavioural intentions in personalising their learning using technology to promote learning inclusion. It is part of a project highlighting the accessibility and means of students of various backgrounds, particularly those deemed disadvantaged. The study’s participants are students from rural or semi-rural areas, pursuing their studies in public higher education institutions in Sarawak or Sabah. The paper’s main aim is to explore the use of personalised learning technologies among these students, as there is a lack of research examining behavioural intentions and how this demographic background affects their usage. Using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) as its theoretical framework, a quantitative approach was employed using questionnaires distributed to undergraduates in four public higher education institutions throughout Sarawak and Sabah. A total of 220 responses were collected, and the researchers employed the AMOS version 24 software to establish the reliability and validity of the questionnaire items, check the model fit, measure structural equation analyses, and examine the primary hypotheses of the theoretical framework. The findings indicate that a good model fit was obtained, with the Performance Expectancy and Student Agency construct demonstrating considerable influence in affecting the behavioural intentions of rural and semi-rural students in personalising their learning using digital technology.